An Analysis of The Sociology of Millennial Women Authors in Indonesia and the Moral Values in Best-Selling Novels - Faisal Kemal; Prima Gusti Yanti; Sukardi Sukardi (Universitas Muhammadiyah Malang, 2025)
This study examines the growing popularity of best-selling novels written by Indonesian millennial women authors, which, surprisingly, present complex moral values relevant to contemporary social dynamics. Contrary to the assumption that contemporary literature merely serves as entertainment, this research aims to uncover the ideological structures underlying these works. Using Lucien Goldmann’s genetic structuralism approach, the study explores the dialectical relationship between textual structures and the authors’ collective consciousness within specific socio-historical contexts. The research employs a qualitative descriptive method that combines textual analysis with interviews, observations, and documentation. The objects of the study focus on three best-selling novels selected based on their popularity, reader engagement, and social relevance. The findings reveal that moral values such as justice, empathy, gender equality, and social responsibility are represented through character conflicts, narrative structures, and the authors’ worldviews. These aspects reflect the collective consciousness structure of the young women’s social class. The study concludes that popular literature not only reflects the social realities of modern Indonesia but also plays an active role in shaping moral values that are contextual, reflective, and transformative for young readers, positioning millennial women’s fiction as both a cultural product and a medium of moral education.